Pengaruh Motivasi Berwirausaha, Lokasi Usaha Dan Media Sosial Terhadap Keberhasilan Usaha (Studi Kasus Pedagang Kuliner Di Kecamatan Sunggal) - Lia Purnama Sari; Zuhrinal M. Nawawi; Nuri Aslami (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the effect of entrepreneurial motivation, business location and social media on the success of culinary traders in Sunggal District. This research was conducted in Sunggal District. Where researchers want to see how much influence entrepreneurial motivation has on business success, how much influence business location has on business success, how much influence social media has on business success and how much influence entrepreneurial motivation, business location, and social media have on business success of culinary traders in Sunggal District . The dependent variable is business success, the independent variables are entrepreneurial motivation, business location, and social media. This research method uses quantitative methods. The data used is primary data. Primary data was obtained using a data collection tool in the form of a questionnaire (questionnaire) from a sample of 86 culinary traders. The analytical tool used is Multiple Linear Regression with the help of the SPSS 25.0 program. The results of the study show that all independent variables have a significant effect on business success. The coefficient of determination is 0.570, which means that business success can be explained by the variable factors of entrepreneurship motivation, business location, and social media of 57.0%. While the remaining 43.0% of the success of the culinary merchant business is explained by other variables that are not included in the analysis model in this study.